Estudio de factibilidad para la creación de una empresa productora y comercializadora de mermelada de uvilla con pepino dulce en la ciudad de Loja. - Saca Chalan, Mayra Yolanda (2023)
Currently in the market, golden berry for its nutritional characteristics and its sour taste are consumed naturally and also are occupied as desserts, bakery and jams, with it is gaining market, but being an exotic fruit and its acidic characteristic, for its preparation requires a high content of sweeteners, This is the research reason ocus on the creation of a company to produce and commercialize grapefruit jam with sweet cucumber in the city of Loja, with the objective of determining the financial viability of the project. This is an exploratory, descriptive and non- experimental study with a quantitative approach, where the deductive method was used, as well as research techniques such as the survey that allowed gathering information on consumer tastes and preferences. The market study determined the unsatisfied demand of 279,919 units of jam for the first year. The technical study identified the company's annual capacity utilization of 80,080 units of jam, maintaining the same production throughout the life of the project. The financial study identified that the project investment amounts to $18,318.38. Finally, the financial evaluation obtained positive results: NPV of $ 21,978.98; IRR of 51.61%; the CBR shows that for every dollar invested, $ 0.10 cents will be earned; the PRC will be 2 years 11 months and 22 days; the sensitivity analysis indicates that the project will support an increase of 3.11% in costs and a decrease in income of 2.83%. Based on the results obtained, it is determined that the implementation of this investment project is feasible.